THE INFORMATIONAL CONTRIBUTION OF VARIED INFLUENCES ON THE DECISION IN THE ANIME CULTURE E-MARKETING - Adrian Nicolae CAZACU (Management & Marketing)
After 1989, we are witnessing a cultural phenomenon in Romania, namely the penetration of a culture revolving around the Japanese animation, commonly referred to as “anime”, and the Japanese manga comics, called the “anime culture”, or otaku culture. Once this culture was assimilated, we later witness the opening of a new entertainment market in Romania, the anime culture market. The promotion and acquisition of the products of this culture is done at this time, almost entirely by electronic means. For this reason, I consider verry important the study of the influencing factors with impact in the context of e-marketing of the anime culture products.